Komposisi Vegetasi Habitat Lutung Jawa (Trachypithecus auratus) di Kawasan Wana Wisata Kalipaingan Kabupaten Pekalongan - Kurniawan, Arif; Baskoro, Karyadi; Jumari, J (Bioma : Berkala Ilmiah Biologi, 2019)
Declining population of Â javan langur caused by several factors such as deforestation and forest fragmentation which are the main habitat for langurs. the vegetation composition of the langur habitat is very important with regard to the density and dominance of trees that have special functions such as tree feed sources, trees at rest and sleeping trees. Â Research on Javan langur habitat had been conducted Wana Wisata Kalipaingan, Pekalongan Regency. Habitat data, as vegetation community and abiotic factor also collected. The research was conducted in March-July 2018. Tree spesies that has the largest INP value is petung bamboo (Dendrocalamus asper) followed by bendo (Atrocorpus elasticus). There are 9 spesies used as feed sources. 3 spesies are used as resting places and 1 tree spesies asa a sleep places.